Emission Factors for Pm2.5, Co, co2 Nox, so2 and Particle Size Distributions from the Combustion of Wood Species Using a New Controlled Combustion Chamber 3ce - Diaz-Robles, L (Elsevier B.V., 2017)
The objective of this research was to determine emission factors (EF) for particulate matter (PM2.5), combustion gases and particle size distribution generated by the combustion of Eucalyptus globulus (EG), Nothofagus obliqua (NO), both hardwoods, and Pinus radiata (PR), softwood, using a controlled combustion chamber (3CE). Additionally, the contribution of the different emissions stages associated with the combustion of these wood samples was also determined. Combustion experiments were performed using shaving size dried wood (0% humidity). The emission samples were collected with a tedlar bag and sampling cartridges containing quartz fiber filters. High reproducibility was achieved between experiment repetitions (CV < 10%, n = 3). The EF for PM2.5 was 1.06 g kg− 1 for EG, 1.33 g kg− 1 for NO, and 0.84 g kg− 1 for PR. Using a laser aerosol spectrometer (0.25–34 μm), the contribution of particle emissions (PM2.5) in each stage of emission process (SEP) was sampled in real time. Particle size of 0.265 μm were predominant during all stages, and the percentages emitted were PR (33%), EG (29%), and NO (21%). The distributions of EF for PM2.5 in pre-ignition, flame and smoldering stage varied from predominance of the flame stage for PR (77%) to predominance of the smoldering stage for NO (60%). These results prove that flame phase is not the only stage contributing to emissions and on the contrary, pre-ignition and in especial post-combustion smoldering have also very significant contributions. This demonstrates that particle concentrations measured only in stationary state during flame stage may cause underestimation of emissions. © 2017 Elsevier B.V.